Net loss : the inner life in the digital age - Smee, Sebastian (Carlton, VIC. : Black Inc., an imprint of Schwartz Publishing Pty Ltd, 2018)
"We live in an age of constant distraction. Is there a price to pay for this? In this superb essay, renowned critic Sebastian Smee explores the fate of the inner life in the age of the internet. Throughout history, artists and thinkers have cultivated the deep self, and seen value in solitude and reflection. But today, with social media, wall-to-wall marketing and the agitation of modern life, everything feels illuminated, transparent. We feel bereft without our phones and their cameras and the feeling of instant connectivity. It gets harder to pick up a book, harder still to stay with it. Without nostalgia or pessimism, Sebastain Smee guides us from the apparent fullness of the app-filled world to a more complex sense of self... If we lose the inner life, Smee asks, what do we lose of ourselves?"--Back cover.
Includes correspondence re 'Follow the leader', pages 57-93 : Katharine Murphy, Scott Ryan, Sean Kelly, Amanda McKenzie, Shireen Morris, Dennis Atkins, Nyadol Nyuon, Norman Abjorensen, Laura Tingle.
Cover title.
Keywords: Internet -- Social aspects; Information technology -- Social aspects; Internet addiction; Self in literature; Australian; Essays